Common knowledge how companies thrive by sharing what they know - Dixon, Nancy M. (Boston, Mass. Harvard Business School Press, 2000)
"Common Knowledge gets to the heart of one of the most difficult questions in knowledge transfer today: What makes a system work effectively in one organization but fail miserably in another? Going beyond "one-size-fits-all" approaches and simple generalities like upper management involvement and cultural issues, this important book will help organizations of every kind construct knowledge transfer systems tailored to their unique forms of "common knowledge" - and in the process create the best kind of competitive advantage there is: the kind that can't be copied."--BOOK JACKET
Keywords: Organizational learning; Business enterprises -- Communication systems; Intellectual cooperation